Analisis Usaha Pedagang Kaki Lima Di Sepanjang Ruas Jalan Ronggowarsito Kota Pekanbaru - Shinta Triwani; Sumarno Sumarno; Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThe study aims to find out how businesses hawkers along Jalan Ronggowarsito Pekanbaru from the of „production factors‟. Data was collected using the techniques of observation and interview. The study was conducted in a descriptive qualitative approach that describe the state of the overall food vendors business based on the concept of production factorsThe results showed that one wagon would take the area of approximately two meters that sometimes blocking the road and causing congestion. Some of the hawkers experienced with the limitation of raw materials supply. Regarding labor, the street food business would employ two to three workers include family members and relatives The average assets held by traders ranged between 1-5 million , the average capital cost per day ranges between Rp 300,000 - Rp 500,000 with an average turnover Rp500.000 - Rp900.000, 150,000 and profit - 350.000. To expand their business, they were also experienced with capital constraints, most traders use their savings to run the business due to lack of official business loan assistance. Dealing with the conclusion, it is suggested to the Department of Industry and SMEs to bring the food traders (hawkers) to be analyzed with the purpose to arrange officially and to administer in a good manner. The result, the area of Ronggowarsito eventually would become one of the hawker centers or culinary folk in Pekanbaru.Keywords : Informal Traders, Hawkers, Factors Of Production